2019
DOI: 10.1002/ijc.32510
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial effects and survival outcomes associated with concordance between tissue and blood KRAS alterations in the pan‐cancer setting

Abstract: We investigated the impact of time interval, primary vs. metastatic biopsy site, variant allele fraction (VAF) and histology on concordance of KRAS alterations in tissue vs. circulating tumor DNA (ctDNA), and association of concordance with survival. Blood and tissue were evaluated by next‐generation sequencing in 433 patients with diverse cancers. Altogether, 101 patients (23.3%) had KRAS alterations: 56, ctDNA (12.9%); 81, tissue (18.7%); and 36, both (8.3%). The overall blood and tissue concordance rate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…It should be noted that the sensitivity of ctDNA for tissue DNA in detecting alterations was lower, compared with that of tissue DNA for ctDNA (57% [29 of 51] versus 88% [29 of 33] for TP53, and 47% [28 of 60] versus 100% [28 of 28] for KRAS, respectively). Other studies have found similar results [45][46][47]. Discordant cases that were positive in tissue and negative in ctDNA have been previously explained by low tumor load in surgically resectable cases [43,44].…”
Section: Discussionsupporting
confidence: 69%
“…It should be noted that the sensitivity of ctDNA for tissue DNA in detecting alterations was lower, compared with that of tissue DNA for ctDNA (57% [29 of 51] versus 88% [29 of 33] for TP53, and 47% [28 of 60] versus 100% [28 of 28] for KRAS, respectively). Other studies have found similar results [45][46][47]. Discordant cases that were positive in tissue and negative in ctDNA have been previously explained by low tumor load in surgically resectable cases [43,44].…”
Section: Discussionsupporting
confidence: 69%
“…By contrast, higher rates of "all same TP53 mutations" categories were observed for colorectal cancer, perhaps reflecting higher frequency of ctDNA detection in this tumor type (14). Interestingly, we previously found colorectal cancers (versus other malignancies) to also have higher concordance between blood and tissue results for KRAS alterations (36).…”
Section: Discussionmentioning
confidence: 73%
“…Regarding histologic effects, overall TP53 concordance of blood vs tissue did not differ between colorectal and noncolorectal cancer, but positive concordance was higher in colorectal cancer (60.9% vs 41.5%; P = 0.02). Previous studies have also shown high concordance for blood and tissue alterations, such as those in the KRAS, NRAS , APC, and BRAF genes, in colorectal cancer (Grasselli et al , 2017; Gregg et al , 2018; Kato et al , 2019; Mardinian et al , 2019).…”
Section: Discussionmentioning
confidence: 87%